Global warming - Parks, Peggy J. 1951-; Gale Group (San Diego, Calif. Lucent Books, 2004)
Discusses scientific evidence that indicates Earth's heat is increasing and the consequences of that warming trend to life, agriculture, and lands.
What is global warming? -- The study of climate change -- The human contribution -- Signs of a warming planet -- Global warming and the future -- A cooler Earth.
Electronic reproduction.
Keywords: Global warming -- Juvenile literature; Climatic changes -- Juvenile literature; Climatology -- Juvenile literature; Electronic books